192k views
0 votes
Last question I need help on

Last question I need help on-example-1

2 Answers

2 votes

( x + 1 )( x )( x - 5 ) =

( x + 1 )( x - 5 )( x ) =

( x^2 - 4x - 5 )( x ) =

x^3 - 4x^2 - 5x

User Martijn Pieters
by
4.5k points
1 vote

Explanation:

the other answer is basically correct.

as the simplest form you create 3 terms for the three given solutions (= the values for when the equation equals 0).

but maybe you need to add " = 0" for the full equation.

User Shermano
by
5.4k points